Implementation of stethoscope disinfection: an observational study on nursing staff practice and knowledge - Şahan, Seda; Güler, Sevil; Korkmaz, Emine (German Medical Science GMS Publishing House, 2024)
Background: Healthcare-associated infections cause high mortality anorbidity, and lack of stethoscope disinfection is one of the reasoor healthcare-associated infections. Nurses who frequently use stetoscopes in the clinic do not disinfect stethoscopes at high rates. This study aimed to identify the frequency of stethoscope disinfection by nurses and their knowledge about the same. Methods: This was a mixed-methods observational study. The quantitave part of the study included 202 nurses, the qualitative part include2. Two researchers who made observations during stethoscope use recorded the procedures the nurses performed on the "Observation Form". Semi-structured in-depth interviews were conducted based on phenomenological methods. Results: 23.7% of the nurses disinfected their stethoscopes before contact with patients, 11.8% after contact with patients and 6.4% before and after contact with patients. The nurses used a stethoscope on an average of 7.42 patients without disinfecting it. In the qualitative interview, some nurses stated that they did not have information about the disinfectants to be used for stethoscopes and their effectiveness. Some of the participants in the present study stated that they did not receive training on stethoscope disinfection and that they did not know that there were guidelines about it.Conclusion: Since there were deficiencies in the implementation of stethoscope disinfection as well as knowledge, the transfer of knowledge in this context must receive more attention in education and training.